Effectiveness of Educational Media on Children's Knowledge of Sexual Violence - rahmah, afiatun; Mirawati, Mirawati; Khairunnisa, Khairunnisa; Baihaqi, Muhammad Ferdy; Ariana, Rahma Alifia; Ariadi, Herman (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2025)
Background: Reproductive health and sexuality education in elementary schools play an important role in shaping children's knowledge and protective behavior. However, the material provided is still limited to the introduction of reproductive organs and general dangers, leading many students to seek information from unreliable sources.Objectives: This study aimed to analyze the effect of booklet media on increasing knowledge about sexual violence among elementary school students in grades III–VI. A preexperimental design with a one group pre-test and post-test was used.Methods: The instrument was a questionnaire containing 20 questions covering basic knowledge about the body, recognition of sexual violence, self-protection, appropriate actions after an incident, and educational understanding.Results: The results of the Wilcoxon Signed Rank test showed a significant increase in knowledge before and after the intervention (p = 0.000). The average pre-test score of 11,26 increased to 16,54 in the post-test. The majority of students who were initially in the moderate and low knowledge categories changed to the good category after being given the booklet.Conclusion: The booklet media has proven to be effective as an educational tool that can be used in promotive and preventive efforts in elementary schools. This intervention can be used as a community midwifery strategy to improve child protection against sexual violence